Analysis of the perception of quality of life of volleyball players: a comparison between genders - Cunha, Renata de Andrade; Morales, Juan Carlos Pérez; Samulski, Dietmar Martin (Brazilian journal of physical education and sport, 2008)
The aim of this study was to analyze and compare the perception of quality of life among female and male volleyball players. 70 players participated in the study (average age of 16.68 ± 2.63 years). The instrument utilized was the Quality of Life Questionnaire for Athletes. The internal consistency was over 0.87. Mann Whitney test indicated a significant difference in situations that promote the quality of life in training environment "group union" and "appropriate intervals of rest/recovery," with higher values for the female players. Significant differences were also observed in the following situations that may affect the quality of life in training: "injuries", "problems of social relationship" and "health problems", with higher values for men. Regarding situations that favor the quality of life in the competitive environment, female players presented significant higher values for "proper planning of competitions". In those situations that may affect the quality of life in competitions, males presented higher values for "injuries", "lack of physical conditioning" and "health problems". One can assume that either in training or competition environments, female players are more concerned with factors related to sport's organization while male players are more concerned with biological aspects. The adoption of procedures aimed at specific issues for each gender may contribute for improving the quality of life and sportive performance of athletes.